2014
DOI: 10.1016/j.jvs.2014.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weekend admission on the outcomes and management of ruptured aortic aneurysms

Abstract: Objective Ruptured aortic aneurysm is a condition with a high rate of mortality that requires prompt surgical intervention. It has been noted that in some conditions requiring such prompt intervention, in-hospital mortality is increased in patients admitted on the weekends as compared to patients admitted on weekdays. We sought to determine if this was indeed the case for both ruptured thoracic and abdominal aortic aneurysm and elucidate the possible reasons. Methods Using the Nationwide Inpatient Sample (NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 23 publications
1
59
0
Order By: Relevance
“…myocardial infarctions, strokes, and pulmonary embolism (1-5). Similar analyses for diagnoses requiring urgent surgery, such as ruptured aortic aneurysms, have also demonstrated inferior outcomes (6). Previous analyses have suggested that outcomes following kidney and liver transplants performed over the weekend are similar to transplants performed during the week (7-10).…”
Section: Introductionmentioning
confidence: 90%
“…myocardial infarctions, strokes, and pulmonary embolism (1-5). Similar analyses for diagnoses requiring urgent surgery, such as ruptured aortic aneurysms, have also demonstrated inferior outcomes (6). Previous analyses have suggested that outcomes following kidney and liver transplants performed over the weekend are similar to transplants performed during the week (7-10).…”
Section: Introductionmentioning
confidence: 90%
“…There is weak evidence showing that time to treatment influences survival adversely. 52,53 This might be have been a contributor to mortality in the EVAR groups of the AJAX and ECAR trials but, for the IMPROVE trial, the time difference was much shorter. Misdiagnosis might also contribute to the mortality rate in the EVAR group because diagnosis, even after CT, can be in doubt.…”
Section: Mortality and Other 30-day Outcomes In The Improve Trial Andmentioning
confidence: 99%
“…Among 5800 ruptured AAA participants, the in-hospital mortality was significantly higher among those participants admitted at weekends than among those admitted during the week (OR 1.32, 95% CI 1.13 to 1.55; p = 0.0004), and only 77% of those admitted at weekends underwent same-day repair, compared with 80% admitted during the week (p = 0.004). 52 Given the large sample size, Groves et al 52 tried to identify factors contributing to the increased (32% higher) mortality at the weekend. It was not related to differential use of EVAR but, at weekends, participants received blood transfusion more often than during the week.…”
Section: Time Of Presentationmentioning
confidence: 99%
“…These results highlight the pitfalls associated with studies of the weekend effect in large databases, and call into question the results of previous studies1 13 showing an apparent weekend effect in the treatment of ruptured AAA. They suggest that two significant effects contribute to, or perhaps even account for, the weekend effect.…”
Section: Discussionmentioning
confidence: 67%
“…The weekend effect was originally highlighted for patients undergoing acute AAA repair in Canada1, and has more recently been explored using the American National Inpatient Sample13. Both studies found a significant effect for patients admitted at the weekend, but used large administrative coding databases, similar to the one found to suffer from inaccuracies in the context of acute stroke7, with no attempt to check diagnostic codes with treating clinicians.…”
Section: Introductionmentioning
confidence: 99%